(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this work we wish to analyze the role of affects in self-translation in Mapuche poetry. We see in the “affective turn” a possibility to understand the bilingual literary production of Mapuche authors as an ethical project of linguistic reappropriation and transgression of cultural limits originated in affects of “genealogical drive” that question the authority of the language of the colonizer, as well as resulting in the generation of “active affects”, inherent to the increase of the degree of expressive potency of the subjects. For this purpose, we set out to trace a cartography of concepts by different thinkers who have reflected upon the relationship between affects and language, from Jacques Derrida to Gloria Anzaldúa, as well as the inescapable contributions of Gilles Deleuze on the study of affects in Spinoza’s Ethics. Also, we will link such concepts with the reflections of five Mapuche poets, Liliana Ancalao, Adriana Paredes Pinda, María Teresa Panchillo, Leonel Lienlaf and Elicura Chihuailaf.